Uji Ekstrak Etanol Daun Pegagan (Centella asiatica L. Urban) terhadap Fertilitas Tikus Putih (Rattus norvegicus L.) Betina pada Tahap Praimplantasi - Yassir Dzulfiqor; Budhi Akbar; Susilo Susilo (Al-Kauniyah: Jurnal Biologi, 2015)
This study aims to test extract ethanol of leaves Pennywort (Centellaasiatica L. Urban) toward fertilitation of female white mice Sprague Dawley strain at the praimplantation. Parameters used implantation (IM), loss of gestation (KGE) and death of pasca-implantation (KPI) after 15 days pregnant.This research conducted from April 2014 in the biology laboratory of UHAMKA, East Jakarta. The sample used 24 rat that divided into four treatment, namely: control(D0), 125(D1), 150(D2 and 175 mgkg-1 bw(D3)with Complete Random Design.The results of data by paired samples test analysis obtained significant differences (p<0,05) between the control group ( D0 ) with the doses 150 mgkg-1 bb (D2) on the decline IM and an increase KGE.On the percentage the average KPI obtained influence is no real different ( p>0.05 ) in all treatment, but a tendency increased the KPI average percentage in the doses 175 mgkg-1 bw (D3).The conclution of this researchis the ethanol extract of leaves Pennywort can reduce the percentage of the average number on implantation (IM) and increase the loss of gestation (KGE) with an effective dose of 150 mgkg-1 bw. Then, the tendency to raise the post-death implantation (KPI) early stage at a dose of 175 mgkg-1 bw.